Endoscopic submucosal dissection of a gastric mass. Issue 4 (2nd October 2019) - Ebrahim, Ahmed; Leeds, Steven G.; Clothier, Jessica S.; Ward, Marc A.
Abstract: This case report describes the first endoscopic submucosal dissection performed at Baylor University Medical Center for high-grade dysplasia of the stomach. The patient, a 76-year-old man with multiple medical comorbidities, presented with 4 months of abdominal pain. Endoscopy found a mass on the lesser curvature, and endoscopic ultrasound confirmed that it did not invade the submucosa. A complete endoscopic resection was performed, alleviating the need for surgical intervention. Endoscopic submucosal dissection offers a minimally invasive treatment for premalignant lesions and early stage cancers of the stomach. Endoscopic resection is as effective as gastrectomy, with less morbidity in select patients with early stage lesions.